Impact of SARS-CoV-2 Virus (COVID-19) Preventative Measures on Communication: A Scoping Review - Ilze Oosthuizen; Ilze Oosthuizen; Gabrielle H. Saunders; Vinaya Manchaiah; Vinaya Manchaiah; Vinaya Manchaiah; Vinaya Manchaiah; Vinaya Manchaiah; De Wet Swanepoel; De Wet Swanepoel; De Wet Swanepoel (Frontiers Media S.A., 2022)
IntroductionFace coverings and distancing as preventative measures against the spread of the Coronavirus disease 2019 may impact communication in several ways that may disproportionately affect people with hearing loss. A scoping review was conducted to examine existing literature on the impact of preventative measures on communication and to characterize the clinical implications.MethodA systematic search of three electronic databases (Scopus, PubMed, CINAHL) was conducted yielding 2,158 articles. After removing duplicates and screening to determine inclusion eligibility, key data were extracted from the 50 included articles. Findings are reported following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) Extension for Scoping Reviews, including the PRISMA-ScR checklist.ResultsStudies fell into three categories: Studies addressing the impacts of personal protective equipment (PPE) and/or distancing on communication in healthcare contexts (n = 20); studies examining the impact of preventative measures on communication in everyday life (n = 13), and studies measuring the impact of face coverings on speech using acoustic and/or behavioral measures (n = 29). The review revealed that masks disrupt verbal and non-verbal communication, as well as emotional and social wellbeing and they impact people with hearing loss more than those without. These findings are presumably because opaque masks attenuate sound at frequencies above 1 kHz, and conceal the mouth and lips making lipreading impossible, and limit visibility of facial expressions. While surgical masks cause relatively little sound attenuation, transparent masks and face shields are highly attenuating. However, they are preferred by people with hearing loss because they give access to visual cues.ConclusionFace coverings and social distancing has detrimental effects that extend well beyond verbal and non-verbal communication, by affecting wellbeing and quality of life. As these measures will likely be part of everyday life for the foreseeable future, we propose that it is necessary to support effective communication, especially in healthcare settings and for people with hearing loss.